2003
DOI: 10.1897/02-459
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomer‐specific biomagnification of α‐Hexachlorocyclohexane and selected chiral chlordane‐related compounds within an arctic marine food web

Abstract: Concentrations of achiral and chiral organochlorine contaminants (OCs), including hexachlorocyclohexane isomers (HCH), chlordane congeners (cis- and trans-chlordane, cis- and trans-nonachlor, MC5, MC7, and U82), and related metabolites (oxychlordane [OXY] and heptachlor exo-epoxide [HEPX]), were quantified in seawater (100 L; n = 6) and biota from the coastal Beaufort-Chukchi Seas food web near Barrow (AK, USA). The biota included zooplankton (Calanus spp.; n = 5), fish species such as arctic cod (Boreogadus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 62 publications
2
48
0
Order By: Relevance
“…The EFs of R-HCH in calanoid copepods in the present study (0.431) were lower than in the coastal Beaufort-Chukchi Seas (0.48) (9), but more similar to EFs from the Northwater Polynya (0.42) (10). Both Hoekstra et al (9) and Moisey et al (10) reported R-HCH EFs in zooplankton similar to those in water, suggesting nonenantioselective bioaccumulation. The EFs of R-HCH in pelagic T. libellula in the present study (0.409) were lower than EFs from the Northwater Polynya (EF ) 0.43, 10), which were both higher than in present T. libellula collected by bottom trawl (EF ) 0.348).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…The EFs of R-HCH in calanoid copepods in the present study (0.431) were lower than in the coastal Beaufort-Chukchi Seas (0.48) (9), but more similar to EFs from the Northwater Polynya (0.42) (10). Both Hoekstra et al (9) and Moisey et al (10) reported R-HCH EFs in zooplankton similar to those in water, suggesting nonenantioselective bioaccumulation. The EFs of R-HCH in pelagic T. libellula in the present study (0.409) were lower than EFs from the Northwater Polynya (EF ) 0.43, 10), which were both higher than in present T. libellula collected by bottom trawl (EF ) 0.348).…”
Section: Resultsmentioning
confidence: 94%
“…transChlordane and cis-chlordane were racemic also in European and North American arctic waters (1), and Arctic cod (Boreogadus saida) (9,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TC and CC were racemic in arctic-subarctic waters between 1994-2001. 26,40) The EF of CC averaged 0.497 in the North Atlantic-Greenland Sea in 2004, 41) while mean EFs of CC (0.516) and TC (0.469) were found south of Iceland in 2008. 42) Depletion of (+) TC was found in the Laurentian Great Lakes Superior, Erie and Ontario (mean EFs 0.474-0.478).…”
Section: Enantioselective Degradation In Soil and Watermentioning
confidence: 99%
“…43) Enrichment of (+) HEPX was found in the central Arctic Ocean (mean EF 0.608), 26) the North Atlantic (mean EF 0.596) 42) and the Great Lakes (mean EFs 0.647-0.658), 43) while HEPX was racemic in the Beaufort Sea. 40) Climate warming is likely to impact algal and microbial communities in aquatic systems through loss of ice cover and consequent increased light intensity, earlier spring phytoplankton blooms, hydrological changes in wetlands which drain into rivers and lakes; and in the ocean, freshening due to lowered salinity.…”
Section: Enantioselective Degradation In Soil and Watermentioning
confidence: 99%